Linked data for the perplexed librarian - Carlson, Scott, 1983-; Lampert, Cory; Melvin, Darnelle; Washington, Anne (ALCTS monograph., 2020)
"A plain-language introduction to the often intimidating field of linked data and the semantic web"--